CNSS Mapping for IA lab exercises - Dodge, R.; Armstrong, Helen (CISSE, 2009)
The number of tertiary institutions gaining recognition as a Center of Academic Excellence in Information Assurance has increased steadily since its inception. Although there is some debate on the desirability to align ‘university education’ with training standards and certifications, such recognition provides a baseline of skills and knowledge upon which the information security industry may rely. The task of developing IA curriculum to meet the needs of the standards compliance is a detailed and time-consuming task, with much duplication of effort across educational bodies. This paper presents the idea of using lab exercises to meet the needs of the CNSS standards, which form the basis of the CAEIA requirements and at the same time provide a meaningful and interesting learning experiences for the students.